Multikinase activity of fibroblast growth factor receptor (FGFR) inhibitors SU5402, PD173074, AZD1480, AZD4547 and BGJ398 compromises the use of small chemicals targeting FGFR catalytic activity for therapy of short-stature syndromes - Gudernova, Iva; Veselá, Ivana; Balek, Lukas; Buchtová, Marcela; Dosedelova, Hana; Kunova, Michaela; Pivnicka, Jakub; Jelinkova, Iva; Roubalova, Lucie; Kozubik, Alois; Krejci, Pavel (Human molecular genetics, 2016)
Activating mutations in the fibroblast growth factor receptor 3 (FGFR3) cause the most common genetic form of human dwarfism, achondroplasia (ACH). Small chemical inhibitors of FGFR tyrosine kinase activity are considered to be viable option for treating ACH, but little experimental evidence supports this claim. We evaluated five FGFR tyrosine kinase inhibitors (TKIs) (SU5402, PD173074, AZD1480, AZD4547 and BGJ398) for their activity against FGFR signaling in chondrocytes. All five TKIs strongly inhibited FGFR activation in cultured chondrocytes and limb rudiment cultures, completely relieving FGFR-mediated inhibition of chondrocyte proliferation and maturation. In contrast, TKI treatment of newborn mice did not improve skeletal growth and had lethal toxic effects on the liver, lungs and kidneys. In cell-free kinase assays as well as in vitro and in vivo cell assays, none of the tested TKIs demonstrated selectivity for FGFR3 over three other FGFR tyrosine kinases. In addition, the TKIs exhibited significant off-target activity when screened against a panel of 14 unrelated tyrosine kinases. This was most extensive in SU5402 and AZD1480, which inhibited DDR2, IGF1R, FLT3, TRKA, FLT4, ABL and JAK3 with efficiencies similar to or greater than those for FGFR. Low target specificity and toxicity of FGFR TKIs thus compromise their use for treatment of ACH. Conceptually, different avenues of therapeutic FGFR3 targeting should be investigated.
Keywords: Chick Embryo; Animals; Catalysis; chondrocyty; pyrimidiny; Cartilage; Achondroplasia; katalýza; Receptor Protein-Tyrosine Kinases; piperaziny; Pyrazoles; lidé; pyrazoly; Mice; tyrosinkinasové receptory; Chondrocytes; signální transdukce; Receptors, Fibroblast Growth Factor; kultivované buňky; myši; Signal Transduction; fenylmočovinové sloučeniny; Cells, Cultured; Benzamides; Pyrroles; benzamidy; Piperazines; chrupavka; receptory fibroblastových růstových faktorů; achondroplazie; Syndrome; zvířata; Phenylurea Compounds; pyrroly; kuřecí embryo; Pyrimidines; syndrom; Humans